Protocolos de avalia????o aer??bia e anaer??bia e efeitos da estimula????o transcraniana por corrente cont??nua sobre o desempenho em teste de corrida de 3000 metros - Madrid, Bibiano (2016)
The present study is composed by four papers with different aims, as follows: 1) Verify the reliability of the Wingate anaerobic test. 2) Verify the reliability of lactate minimum protocol with induction of hyperlactatemia individualized by ratings perceived exertion. 3) Verify the efficiency of a new submaximal protocol for aerobic evaluation, with workloads determination by ratings perceived exertion, denominated RPE-13, in identify the intensity of exercise associated at maximal lactate steady state and lactate minimum. 4) Verify the influence of anodal transcranial direct current stimulation on left temporal lobe in the heart rate variability and in the running of 3000 meters. The Wingate study had a sample composed by 15 cyclists that performed three Wingate tests. The lactate minimum study had a sample composed by 20 university students active physically that performed two times the test. In the study with RPE-13 the sample was formed by 11 young adults active physically that performed three tests, the RPE-13, lactate minimum and maximal lactate steady state. Yet, in the study with anodal transcranial direct current stimulation the sample was composed by 11 amateurs??? runners that performed of the 3000 meters test in two conditions, in the anodal stimulation and Sham condition (placebo). The tests of Wingate and lactate minimum showed good reliability. The RPE-13 test showed to be efficient to identify an intensity of exercise associated at maximal lactate steady state and lactate minimum. Therefore, the transcranial direct current stimulation changed the heart rate variability, increasing the chronotropic reserve and improving the performance in running of 3000 meters in mean 10 seconds.